Postgraduate course for stomatologists about medical emergencies during professional practice - Isis Anastasia Rojas Herrera (Centro Provincial de Información de Ciencias Médicas, 2024)
Introduction: During stomatological practice, medical emergencies can be presented related to the procedures carried out or the patients' underlying diseases; however, there are deficiencies in the care to them. Objective: To expose the generalities of the postgraduate course for stomatologists about medical emergencies during the professional practice and the criteria emitted by their participants. Methods: A descriptive pedagogic investigation was carried out, where 62 students from the Faculty of Stomatology of the University of Medical Sciences in Havana participated, since November, 2018 to December, 2022. The following variables were analyzed: topics, objectives and system of knowledge and abilities. Also, the technique of positive, negative and interesting was used. Results: This course had 5 topics: the first one, dedicated to the most frequent medical emergencies generalities during dental care and the particular characteristics when making the medical record; the second and third topics were dedicated to the risk factors and care to these emergencies; the fourth, to the use of medications and possible interactions and, the fifth, to clinical experiences. The students contributed positive, negative and interesting criteria. Conclusions: The designed course offered knowledge and abilities to the student that are not provided in undergraduate and postgraduate subjects of the specialties, which contributed to improve the comprehensive dental care of patients. The participants offered favorable criteria about the structure, relevance and scientific value of this course.